الدراسة الفنية لنظام توليد طاقة كهربائية ثنائي المصادر (شمسي- ريحي) - الحايك غسان; حسن عزت; ميهوب عمار (Latakia University Journal -Engineering Sciences Series, 2016)
تعد طاقة الرياح والشمس من أهم مصادر الطاقة المتجددة بسبب وفرتها واقتصاديتها, ويمكن الاستفادة من هذين المصدرين للطاقة المتجددة في منطقة قطينة التابعة لمحافظة حمص, لتصميم وبناء نظام طاقة كهربائي ثنائي المصادر (شمسي - ريحي) سيتم الاعتماد على المنحني اليومي لكل من سرعة الرياح وشدة الإشعاع الشمسي للمنطقة المدروسة. تمَّ في هذا البحث دراسة تصميم نظام شمسي ريحي هجين باختيار مكوناته المتوفرة في السوق المحلية لجهة مواصفاتها الاسمية الفنية, وذلك استناداً على الدراسات الفنية والاقتصادية, والمعايير العالمية الموافقة. أظهرت النتائج التي حصلنا عليها أن لدينا فائض خلال العام حوالي (1246.7 Kw/Year) لصالح المستهلك, مما يجعل النظام مجدي اقتصاديا من الناحية الاستثمارية, كما اظهر البحث أنه بحاجة لمصدر إضافي لتغذية الحمولة وشحن المدخرات باستطاعة 3360.2 W/Day)) بما يشكل (50.4%) من حجم الحمولة. إضافة إلى النتائج العملية فانه يقدم قاعدة بيانات نظرية سواء للباحث أو للمستثمر في مجال الطاقات المتجددة وخصوصاً لجهة كفاءة اختيار مكونات النظام. Solar and wind energy is considered as one of the best renewable energy resources because it Available and economical . We can take advantage of these two resources of renewable energy in Katina area in Homs for designing and building a bilateral resources (solar-wind) electric power system, depending on the daily bending of the wind speed and the solar radiation intensity in the studied area. This research studies the design of a hybrid wind and solar system by selecting its components that available in the local market in terms of their nominal, technical specifications, based on the technical and economic studies and the corresponding international standards. The obtained results showed that we have approximately (1246.7 Kw/Year) surplus during the year for the benefit of consumers, which makes the system economically feasible for investment, as explained in research needs an additional resource to feed the load and charge the energy-savings with (3360.2 w/day) that constituting (50.4 %) of the volume of the load in addition to the practical results provides a theoretical database, whether for the researcher or the investor in the field of renewable energies, particularly in terms of the efficiency of selecting the system’s components.